Red Colour, Widowhood, and the Struggle for Social Citizenship in Nepal: A Qualitative Social Work Inquiry (Khwopa Journal, 2026)
In Nepal, widowhood is governed by a patriarchal normative order that systematically excludes widows from markers of social auspiciousness, most visibly through the prohibition on wearing red — the colour of marital life and sacred femininity in Hindu society. The Rato Kapada Andolan (Red Colour Movement) emerged as an organised feminist response, mobilising widowed women and civil society actors to assert widows' right to wear red and to reclaim full social citizenship. This study examines the movement's origins, agendas, achievements, and structural limits from a social work perspective. Drawing on qualitative in-depth interviews with thirteen purposively selected widowed women in Kathmandu district, the analysis is framed by feminist social movement theory, social justice theory, and social work empowerment frameworks, cross-cut by an intersectional lens attending to caste, class, age, and geography. Findings show that the movement has produced meaningful gains in psychological empowerment and community norm disruption, particularly in urban areas, but that these gains are structurally uneven. Widows lacking economic independence or residing beyond the movement's organisational reach remain outside its transformative arc. The study argues that symbolic cultural change is insufficient without concurrent legal protection, economic empowerment, and deliberate outreach to underserved populations, including Dalit widows facing compounded exclusion.